PERILAKU PEMBERANTASAN SARANG NYAMUK DAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) JAKARTA BARAT - Mils, Brenda; Febrianti, Thresya (STIKES Cendekia Utama Kudus, 2024)
Based on the Jakarta Health Department's surveillance report in 2018, the highest IR for DHF cases was in West Jakarta with an IR of 36.96 / 100,000 population and the highest in Grogol Petamburan District was the highest IR of 68 / 100,000 population. The aims this study to analysis the relationship between the behavior of eradicating mosquito nets with the incidence of DHF in Grogol Petamburan District. Stdy design is a cross-sectional with a sample of 219 respondents The sampling technique used random sampling. Analysis with Chi-Square ?=0,05. The prevalence of DHF in as much as 16% of 219 respondents. The related variables based on the analysis are the drainage behavior of the water reservoir (p-value = 0.003 OR: 3.22 95% CI: 1.431-7.250), the behavior of closing the water reservoir (p-value = 0.004, OR: 2.88 95% CI: 1,372-6,048), behavior of disposing / recycling used goods (p-value = 0.01, OR: 2.601 95% CI: 1,236-5,480), behavior of maintaining larvae eating fish (p-value 0.01, OR: 3,356 95% CI: 1,243-9,064), the behavior of using abate powder in a water reservoir (p-value 0.03, OR: 2.76 times greater than the incidence of DHF (95% CI: 1,020-7,482), the behavior of installing wire gauze (p-value: 0.002, OR: 3.1 95% CI: 1,474-6,518), behavior of hanging clothes (p-value = 0,000, OR: 9.74 95% CI: 3.841-24.728), behavior of using anti-drug mosquito (p-value: 0,000, OR: 5.38 95% CI: 2,136-13,596). There is a relationship between the behavior of eradicating mosquito nests related to the behavior of draining, closing, throwing / recycling, maintaining larvae, using abate powder, using wire mesh, changing clothes, and using mosquito repellent. The need to increase the behavior of eradicating mosquito nests in the community related to the behavior of draining, closing, disposing of / recycling, maintaining larvae, using abate powder, using wire mesh, changing clothes and using mosquito repellent to prevent the occurrence of DHF.